Minat Berwirausaha Dampak Efikasi Diri, Motivasi dan Lokus Kendali Pada Mahasiswa - Pratama , Andy Putra; Widyastuti, Maria (Jurnal Keuangan dan Bisnis, 2021)
Higher education in a place of final educationwhich has an important role in creating human resources who are able to compete in the world of work. Business development that is done by students is growing, especiallyin the city of Surabaya. Tecresearch of population was Surabaya students the samples were determinated using the simple random sampling method. Data were collected by means of a questionnaire to 75 responden. The purpose of the  research is to determine the interest in doing business is the impact of Self – Efficacy, Motivation and locus of control. The results of study show that interest in doing business is a significant impact of self-ethification, this can be seen from t count3.801>t table 1.99394 and a significant value of 0.00< 0.05 and from the control locus it can be seen from t count -3.081>-1.99394 and the significant value is 0.003<0.05, while motivation has no impacton the interest in doing business, it can  be seen from the t count 1.565< t table 1.99394 and the significant value 0.112 > 0.05. So it can be concluded that interest in trying to impact to impact from of self-ethics and locus of control